Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Geometric Progression (Solution) Final

Download as pdf or txt
Download as pdf or txt
You are on page 1of 12

GEOMETRIC PROGRESSION

1. 9th term of G.P. t 9 , first term a = 2 , Common ratios = 6 = 3 ,


2
9−1 8
t 9 = ar = 2(3) = 2 × 729 = 1458
6
2. Let n term of G.P is 243 2 ∴ ar n−1 = 243 2 , 2 3( ) n −1
= 243 2 [ Q a = 2 , r =
2
= 3]
n −1
n −1
or, ( 3) n −1 5
= 3 or, 3 2
= 35 or,
2
= 5 or, n − 1 = 10 or, n = 11
CLASS XI (SOLVED PAPER)

∴11 th term of G.P. is 243 2 .


3. First term a = 2 2 = 20 . 6th term is 16 78 = 135
8
. Let common ration = r
9 9
5
135 20 5 135 135 × 9  3  3
∴ ar 6−1 = or, r = or, r 5 = =   or, r =
8 9 8 20 × 8  2  2
20 3 10 10 3 3 15 15 3 45
∴x = × = , y = × = 5 , z = 5× = , w = × =
9 2 3 3 2 2 2 2 2 4
∴ The value of x, y, z , w are 10 ,5, 15 , 45
3 2 4
4. The product of three numbers in G.P is 27 .
8
Let three numbers are a , a, ar .
r

r 8 2
3
∴ a × a × ar = 27 or, a 3 = 3 or, () a = 3 ∴ Middle term is 3 .
2 2
m + n −1
5. The given condition u m+ n = a (r ) [ let a = first term , r = common ration ]
p
or, ar m+ n−1 = p or, a =
r m+ n−1
m − n−1 p Q P P
Again , U m−n = Q , a (r ) = Q or, m+ n−1 .r m−n−1 = Q or, r −2 n = or, r 2 n = or, r n = ±
r P Q Q
p −n p p Q
∴U m = ar m−1 = m + n −1
.r m−1 = p (r ) = n
=± = ±P = ± PQ (proved)
r r P
Q
P
6. If the n th term of a G.P. is 2 2 n−1 , t n = 2 2 n−1
S 4 = t1 + t 2 + t3 + t 4 [ S 4 = the sum of first four terms] = 2 + 2 3 + 2 5 + 2 7

=
(
2 44 − 1
=
)
2(256 − 1) 2 × 255
= = 170 . Required Sum is 170.
4 −1 3 3
(3 )
4
(2 ) 16
4
7. The given condition ar 4 = 1 or, a 2 = 1 or, a = 3 = 81

∴ Required value t18 = ar17 = a (2 ) = 81 (2 ) = 2 = (2 )


17 17 13 13
3 16 3 3 3 13

8. Let, r be the common ratio of the G.P.


t3 1 4r 2 1 1 1
= or, 6 = or, 4 = or, r 4 = 81 ∴ r = ±3
t7 81 4r 81 r 81
9
∴ t10 = 4 ⋅ r 9 = 4(± 3) = ±78732

1
b4 1 b r3 1 1 1
9. = or, 1 5 = or, 2 = or, r 2 = 4 ∴ r = ±2
b6 4 b1r 4 r 4
216
Again, b2 + b5 = 216 or, b1r + b1r 4 = 216 or, b1 =
r + r4
216 216
For r = 2 , b1 = = = 12
2 + 16 18
216 216 108
For r = −2 , b1 = = =
− 2 + 16 14 7

10. i) S12 =
(
12
a r −1 )
[ a = first term = 1 , r = Common ratio = 2 ] =
12
1 (2 ) − 1
= (38656 − 1)
{ }
r −1 2 −1
= 38655
n−1 n −1 5
3125 5 3125 5 5
ii) Let n th term in ∴ (2 )  = or,   =   or, n − 1 = 5 or, n = 6 .
16 2 16 2 2
 5  6

2  − 1 15625 
2 − 1
∴ S6 =
a r6 −1 (= 
)
 2  
=  64  = 4 15625 − 64  = 1 {15561} = 5187
 
r −1 5 5−2 3 64  48 16
−1
2 2
11. S n = p and S 2 n = 3 p

∴ S 2 n = 3S n or,
a r 2n − 1 (
= 3⋅
a rn −1 ) ( )
or, (r n + 1)(r n − 1) = 3(r n − 1)
r −1 r −1
or, r n + 1 = 3 (Q r ≠ 1 )
or, r n = 2

∴ S3n =
( =
)
a r 3n − 1 a r n − 1 2 n ( )[
r + r n + 1 = p 22 + 2 + 1 = 7 p . ] ( )
r −1 r −1
12. S be the of n terms in a G.P. S =
a rn −1 ( )
[ a = first term , r = Common ratio ]
r −1
P = a × ar × ar 2 × − − − − ar n−1 = a n .r 1+ 2+3+ −− + n−1 = a n r n (n−1) , P 2 = a 2 n .r n (n−1)
1 1 1 1 11 1 1 1  1 ( 1 n − 1)
R= + + 2 + − − − + n−1 =  0 + + 2 + − − − + n−1  = . r 1
a ar ar ar a r r r r  a r −1
1 1 (r n − 1)
= . .
a r n−1 r − 1

 =
n

)
 S  a r − 1 ar (r − 1)
n−1
S
= a 2 r n−1 .
  =a r
2 n n ( n −1)
n

= P 2 (proved)
n
 
R r − 1 r − 1  
R

13. The Sum of 2n terms of a series in G.P. is 2 R .


a r 2n − 1 ( )
= 2 R ------ (1) [ a = first term
r −1
r = Common ratio]
1 1 1 11 1 1 1 
Again , R = + + − − − − + 2 n−1 =  0 + + 2 + − − − + 2 n−1 
a ar ar a r r r r 
1
1 2n − 1 1 r −1 2n
= . r1 = 2 n−1 . --------------- (2)
a r −1 ar r −1
Let the product of the terms is P
P = a × ar × ar 2 × − − − − ×ar 2n −1 = a 2 n × r1+ 2+ − − 2 n −1 = a 2n r n(2 n−1)
(1) and (2) we get

2.
r 2n − 1 1
. 2 n−1 =
a r 2n − 1 ( )
. 2 = a 2 r 2 n−1 , 2 n = a 2 n r n (2 n−1) or, p = 2 n ∴ p = 2 n
r − 1 ar r −1
2
14. Let ar , a, ar be the three numbers in G.P.
The given Condition a × a × ar = 729 , a 3 = 729 or, a 3 = 9 3 or, a = 9
r
The Sum of their product in pairs is 351
or, a .a + a ar + a.ar = 351 or, a 2 1 + 1 + r = 351
r r
[r ]
351 13 1 10
or, 1 + r + 1 = = or, r + =
r 81 3 r 3
or, 3r 2 + 3 − 10r = 0 or, 3r 2 − 10r + 3 = 0
or, 3r 2 − 9r − r + 3 = 0
or, 3r (r − 3) − 1(r − 3) = 0
or, (r − 3)(3r − 1) = 0 or, r = 3, r = 1
3
∴ The three terms are 3,9,27 or, 27,9,3 .
15. The three terms are a , a, ar . The given Condition, a + a + ar = 21 or, a 1 + 1 + r = 21 ------ (1)
r r
( r
)
a2  1 
Again , 2
+ a 2 + a 2 r 2 = 189 or, a 2 1 + 2 + r 2  = 189 --------------------------------------------(2)
r  r 
(1)2
(
a2 1+ 1 + r
r
)2 = 212 or, a 1 + r1 + r
2
2
2
r
2 
+ 2r + 2  = 212
+

 1   1
or, a 2 1 + 2 + r 2  + 2a 2 1 + r +  = 21 × 21
 r   r
or, 189 + 2.a × 21 = 21 × 21
252
or, 42a = 441 − 189 = 252 or, a = = 6.
42
or, 1 + 1r + r = 21
6
= 72 or, r + 1 = 7 − 1 = 52
r 2
2r + 2 − 5r = 0 or, 2r − 5r + 2 = 0 or, 2r − 4r − r + 2 = 0 or, 2r (r − 2 ) − 1(r − 2 ) = 0
2 2 2

or, r = 2 , r = 12
∴ The three terms are 3,6,12 or, 12,6,3 .
16. a = first term . n th term is l . Let r be Common ratio ∴ ar n−1 = l ,
let r be common ratio ∴ ar n−1 = l -------------- (1)
Again p the product of first n terms of a G.P.
n ( n −1)
∴ P = a × ar × ar 2 × − − − − − ar n−1 = a n r 1+ 2+3+ − −− n−1 = a n r 2
or, p 2 = a 2 n .r n ( n−1) = (al ) [ from equation (1)] (proved)
n

17. S1 , S 2 , S 3 be respectively the sums of first n,2n and 3n terms of a G.P.


a (r n − 1) a(r 2 n − 1) a (r 3n − 1)
∴ S1 = [ a = first term , r = Common ratio ] , S 2 = , S3 =
r −1 r −1 r −1
a (r − 1)  a (r − 1) a (r − 1)
n 3n 2n
a 2
L.H.S, S1 (S 3 − S 2 ) = 
r −1  r −1
− =
r − 1  (r − 1) 2
r 2n − 1 − r n + 1
2
[ ]
=
( )
a 2 r 2n r n − 1
2

∴ S1 (S 3 − S 2 ) = (S 2 − S1 ) (proved)
2

(r − 1)2

3
 1 
11 − n 
 1 
18. S n = 
2  2
= 21 − n  = 2 − n
1  2  2
1−
2
1 2 1 2 1
By question 2 − S n < or, 2 − 2 + n < or, n < or, 2 n > 200
100 2 100 2 100
Q 28 = 256 > 200 > 128 = 2 7 ∴ Least value of n = 8 .
b c
19. a, b, c are in G.P. ∴ = = k (let) . b = ak , c = bk = ak 2
a b
2
a + ab + b 2
a 2 + a.ak + a 2 k 2 a 2 (1 + k + k 2 ) 1
L.H.S, = = =
ab + bc + ca a.ak + ak .ak 2 + ak 2 .a a 2 k (1 + k + k 2 ) k
a+b a + ak a (1 + k ) 1 a 2 + ab + b 2 a + b
R.H.S, = = = ∴ = (proved)
b + c ak + ak 2 ak (1 + k ) k ab + bc + ca b + c
20. The given series,
2 2 2 2
 1  2 1   3 1   4 1 
x +  +x + 2  + x + 3  +x + 4  + − − − − −
 x  x   x   x 
 1   1   1 
=  x 2 + 2 + 2  +  x 4 + 4 + 2  +  x 6 + 6 + 2  + − − − − − up to n terms
 x   x   x 
1 1 1
= ( x 2 + x 4 + x 6 + − − − − up to n terms) + ( 2 + 4 + 6 + − − up to n terms) + 2n
x x x
1   1 
n

2 
1−  2  
=
{(2 4
) +
}
x x − 1 x   x  
2
+ 2 n =
(
x 2 x 2n − 1
+
)
x 2n − 1
+ 2 n =
x 2n − 1  2 1 
x + 2 n  + 2n
2
x −1  1  2
x −1 2n
x x −1 2
( )
2
x −1   x 
1 − 2 
 x 
21. The given Condition ,
S1 = n
S2 = 2n − 1
3n − 1
S3 =
2
--------------
--------------
nh − 1
Sn =
n −1
L.H.S ,
2.3n − 1
(
S1 + S 2 + 2 S 3 + 3S 4 + − − − − (n − 1)S n n + 2 n − 1 + )+ 3.
(4 n − 1) + − − −(n − 1) (n n − 1)
2 3 n −1
= n(2 + 3 + 4 + − − − − + n ) − (n − 1) = 1 + 2 + 3 + 4 + − − − + n = R.H.S (proved)
n n n n n n n n

22. u1 , u 2 , u3 ,− − − form a G.P. with Common ratio k ∴ u k = u1r k −1


The sum of u1u 2 + u 2u3 + − − − + u n u n+1 = u1u1k + u1k .u1k 2 + − − − − +u1k n−1.u1k n

= 1 2
[
u 2 k (k 2 ) − 1
n
] [ ]
u 2 k (k 2 ) − 1 u12 k (k 2 n − 1)
= 1 2 =
n

k −1 k −1 k 2 −1

4
23. i) S n = 1 + 3 + 7 + 15 + 31 + − − − − − − − − upto n terms
= (2 − 1) + (4 − 1) + (8 − 1) + (16 − 1) + (32 − 1) + − − − − upto n terms
= ( 2 + 4 + 8 + 16 + 32 + − − − − − − upto n terms) − n
2(2 n − 1)
= − n = 2 n +1 − 2 − n .
2 −1
ii) S n = 1 + 4 + 13 + 40 + − − − − − − − − upto n terms
1
= [ 2 + 8 + 26 + 80 + − − − − − − upto n terms]
2
1
= [(3 − 1) + (9 − 1) + (27 − 1) + (81 − 1) + − − − − upto n terms ]
2
1
= [(3 + 9 + 27 + 81 + − − − − − − upto n terms ) − n]
2

= 
(
1  3 3n − 1 )
 3
− n  = 3n − 1 − n
1
( )
2  3 −1  4 2
b c d
24. i) a, b, c, d are in G.P. ∴ = = = k (let) or, b = ak , c = bk = ak 2 , d = ck = bk 2 = ak 3
a b c
b2 + c2 a 2k 2 + a 2k 4 k 2 1 + k 2
= = = k
(
2
,
)
c2 + d 2
=
a2k 4 + a 2k 6
=
k2 k2 + k4
= k2
( )
a 2 + b2 a 2 + a 2k 2 1+ k2 b 2 + c 2 a 2 .k 2 + a 2 .k 4 k2 + k4
b2 + c2 c2 + d 2
∴ 2 2
= 2 2
∴ a 2 + b 2 , b 2 + c 2 , c 2 + d 2 are in G.P.
a +b b +c
ii) a, b, c and d are in G.P. Let b = ar , c = ar 2 , d = ar 3
L.H.S , (b − c )2 + (c − a )2 + (d − b )2
= (ar − ar ) + (ar 2 − a ) + (ar 3 − ar )
2 2 2

[
= a 2 r 2 + r 4 − 2 r 3 + r 4 + 1 − 2 r 2 + r 6 + r 2 − 2r 4 ]
= a (r − 1) = (ar 3 − a ) = (d − a ) = (a − d ) = R.H.S = proved .
2 3 2 2 2 2

iii) a , b , c and d are in G.P.


Let, b = ar ∴ c = ar 2 , d = ar 3
L.H.S. = (a 2 + b 2 + c 2 ) (b 2 + c 2 + d 2 )
= (a 2 + a 2 r 2 + a 2 r 4 )(a 2 r 2 + a 2 r 4 + a 2 r 6 )
= a 2 (1 + r 2 + r 4 ) ⋅ a 2 r 2 (1 + r 2 + r 4 )
[
= a 4 r 2 (1 + r 2 + r 4 ) = a 2 r (1 + r 2 + r 4 ) ] 2

= (a ⋅ ar + ar ⋅ ar + ar )
2 2 2
⋅ ar 3
2
= (ab + bc + cd ) = R.H.S.
25. The given Condition 6 th term is 56 , first term is 7 . ∴ 74 r 5 = 56 or, r 5 = 32 or, r = 2
4
∴ Four geometric means between 7 and 56 are 7 ,7,14,28 .
4 2
n +1 n +1
x +y n + 12 n + 12
26. By question = xy or, x n+1 + y n+1 = x y+y x
x + yn
n

n+ 1 n+ 1
or, x n +1 + y n +1 = x 2 y + y 2 x
n+ 1
or, x n+1 ( x− y = y ) 2 ( x− y )

5
n+ 1 n+ 1
or, x 2 =y 2 [ Qx ≠ 0]
n+ 1 0
or,  x  =  x  or, n + 12 = 0 or, n = − 12
2
 y  y
27. t n = 2.3n−1 + 1
t1 = 2.30 + 1
t 2 = 2.31 + 1
t 3 = 2. 3 2 + 1
----------------
----------------
t r = 2.3r −1 + 1
____________
1(3r − 1) 2(3r − 1)
( )
S = 2 30 + 31 + 32 + 33 + − − − + 3r −1 + r = 2.
3 −1
+r =
2
+ r = 3r + r − 1 .

28. t n = 3n + 2n [ By the question ]


t1 = 31 + 2.1
t 2 = 32 + 2.2
t 3 = 33 + 2.3
----------------
----------------
t n = 3n + 2.n
_____________
( )
S = 3 + 32 + 33 + − − − − − + 3n + 2(1 + 2 + 3 + − − − + n )
3(3 − 1) n
n(n + 1) 3 n 3 3
=
3 −1
+ 2.
2 2 2
[ 2
]
= (3 − 1) + n(n + 1) = 3n − 1 + 2n 2 + 2n = 3n + 2n 2 + 2n − 1 .[ ]
29. i) 3 + 33 + 333 + − − − upto n terms
3
= [9 + 99 + 999 − − − − upto to n terms ]
9
3
= [(10 − 1) + (100 − 1) + (1000 − 1) + − − − − upto n terms ]
9
3 3 10(10 n − 1) 3n
= [(10 + 100 + 1000 + − − − upto n terms ) − n ] = . −
9 9 10 − 1 9
3 10 n 3n 10 n 3n
= . (10 − 1) − = (
10 − 1) −
9 9 9 27 9
ii) 0.6 + 0.66 + 0.666 + − − − − upto n terms
6
= [9 + 99 + 999 + − − − upto n terms ]
9
6
= [(1 − .1) + (1 − .01) + (1 − .001) + ----- upto n terms]
9
6
= [ n − (.1 + .01 + .001 + − − − − upto n terms )]
9
6n 6 1 1 1 6n 6 101 (1 − 101 n )
= − [ + + + − − − upto n terms ] = − .
9 9 10 100 1000 9 9 1 − 101
6n 6 1  1  6 1 1 
= − . 1 −  =  n − 1 −  .
9 9 9  10n  9  9  10n  

6
30. i) t n = (n th term of 1,3,5,7,− − −) × (nth term of 1,4,4 2 ,− − −) = (2n − 1).4 n−1
S = 1 + 3.4 + 5.4 2 + 7.4 3 + − − − − − + (2n − 1)4 n−1
4 S = 1.4 + 3.4 2 + 5.4 3 + − − − − − + (2n − 3)4 n−1 + (2n − 1)4 n
_________________________________________________
− 3S = 1 + 2.4 + 2.4 2 + 2.4 3 + − − − − − + 2.4 n−1 − (2n − 1)4 n
2.4(4 n−1 − 1) 2.4 n − 8
=1+ − (2n − 1)4 n = 1 + − (2n − 1)4 n
4 −1 3
1 1 1
[ ] [ ] [
= 3 + 2.4 n − 8 − (6n − 3).4 n = − 5 + (2 − 6n + 3)4 n = − 5 − (6n − 5)4 n
3 3 3
]
1
[
S = 5 + (6n − 5)4 n .
9
]
ii) S = 1.3 + 2.32 + 3.33 + − − − − + n.33
3S = + 1.32 + 2.33 + − − − − +(n − 1)3n + n.3n+1
_______________________________________
− 2 S = 3 + 32 + 33 + − − − − − − +3n − n.3n+1
3(3n − 1) 3
= − n.3n+1 = (3n − 1) − n.3n+1
3 −1 2
n
3 3  3 3 3
= (3n − 1) − 3n.3n = 3n  − 3n  − = (3 − 6n ) −
2 2  2 2 2
1
[ ]
= 3n (3 − 6n ) − 3
2
1
[ ]
or, S = 3 − 3n (3 − 6n ) .
4
1 3 5 2n − 1
iii) S = + 2 + 3 + − − − +
2 2 2 2n
1 1 3 2n − 3 2n − 1
S = + 2 + 3 +−−−+ + n
2 2 2 2n 2 +1
______________________________________
1 1 1 1 1 (2n − 1)
S = + 2. 2 + 2. 3 + − − − − + 2. n −
2 2 2 2 2 2 n+1
1 1 1 1 1  1
= +  + 2 + 3 + − − − + n−1  − (2n − 1). n+1
2 2 2 2 2  2
1
1 
2 1 − n −1 
= + 
1 2  2n − 1
− n+1
2 1 − 12 2
1 2 n−1 − 1 2n − 1 1 2 n−1 − 1 2n − 1
= + n−1 − n+1 or, S = + − n+2 .
2 2 2 4 2n 2
31. r th term of a series is (2r + 1).2 . ∴ t n = (2n + 1)2
r n

S = t1 + t 2 + t3 + − − − + t n
S = 3.2 + 5.2 2 + 7.2 3 + − − − + (2n + 1).2 n
2S = 3.2 2 + 5.2 3 + − − − − + (2n − 1).2 n + (2n + 1)2 n+1
________________________________________________
− S = 3.2 + 2.2 2 + 2.2 3 + − − − + 2.2 n − (2n + 1)2 n+1
= 2 + 2.2 + 2.2 2 + 2.2 3 + − − − + 2.2 n − (2n + 1)2 n+1
2.2(2 n − 1)
=2 − (2n + 1)2 n+1
2 −1
7
( )
= 2 + 4 2 n − 1 − 2n.2 n+1 − 2 n+1
= 2 + 4.2 n − 4 − 4n.2 n − 2.2 n
= 2 n (4 − 4n − 2 ) − 2 = 2 n (− 4n + 2 ) − 2 . S = 2 − (2 − 4n )2 n .
1(x n − 1) 1
32. t n = 1 + x + x 2 + x 3 + − − − − + x n−1 =
x −1
=
x −1
[xn − 1 ]
1
tn =
1− x
[
1 − xn ]
1
t1 =
1− x
[1 − x1 ]
1
t2 =
1− x
[
1 − x2 ]
_---------------------
--------------------
1
tn =
1− x
[
1 − xn ]
___________________

S=
1
[ (
n − x + x 2 + x3 + − − − + x n = )] n

1 x xn − 1
.
( =
)
n

( )
x 1 − xn
(proved)
1− x 1− x 1− x x −1 1 − x (1 − x )2
33. a, b, c are in G.P. ∴ b = ar , c = ar 2 (let)
1 1 2 1 1 2
+ = or, 2
+ = 2
b−c a−b c−a ar − ar a − ar ar − a
1 1 2
or, + =
ar (1 − r ) a (1 − r ) − a (1 + r )(1 − r )
1+ r 2
or, =
ar (1 − r ) − a (1 + r )(1 − r )
2
or, a (1 + r ) = −2ar or, a + 4ar + ar 2 = 0
or, a + 4b + c = 0 [ ar = b, ar 2 = c ]
34. Let A and G be the arithmetic and geometric means respectively of two positive numbers
x+ y
x and y . Then A = and G = ± xy
2
Since x and y are positive numbers , hence it is evident that A > G when G = − xy
Therefore, we are to show A ≥ G when G = xy .
x+ y x + y − 2 xy
we have A − G = − xy =
2 2
1 1
x + y − 2. x . y  =
( ) ( ) ( )
2 2 2
or, A − G = x − y ≥ 0 ∴ A − G ≥ 0 or, A ≥ G
2 
 2
Hence , the arithmetic mean of two positive numbers can never be less than geometric mean.
x+ y
= 15 or, x + y = 30 ------------------ (1) xy = 9 or, xy = 81
2
(x − y )2 = (x + y )2 − 4 xy = 30 2 − 4.81 = 576 = 24 2 , x − y = ±24 ------------------ (2)
(1) + (2) gives 2 x = 54 or, 6 ∴ x = 27 or, 3 when x = 27 then y = 30 − x = 30 − 3 = 27
Therefore , the required numbers are 27,3 .

8
35. Let, the two numbers are x and y (x > y > 0 )
x+ y 2
∴ = 2 xy or, (x + y ) = 16 xy
2
2 2
∴ (x − y ) = (x + y ) − 4 xy = 16 xy − 4 xy = 12 xy
2
x+ y  16 4 x+ y 2 x 2+ 3
∴   = = or, = or, = .
x− y  12 3 x− y 3 y 2− 3
b c
36. i) = [ Q a, b, c are in G.P.] or, b 2 = ac -------------- (1)
a b
x, y be the A.Ms between a, b and b, c respectively
a+b b+c
∴x = or, b = 2 x − a ---------------- (2) , y = or, b = 2 y − c ------------------ (3)
2 2
(2) × (3) b 2 = (2 x − a )(2 x − c ) or, b 2 = 4 xy − 2 xc − 2ay + ac
or, ac = 4 xy − 2 xc − 2ay + ac [ Q b 2 = ac ]
or, 4 xy = 2 xc + 2ay or, xc + ay = 2 xy
a c
or, + = 2 (proved)
x y
ii) Again , a = (2 x − b ) from equation (2) , c = 2 y − b from equation (3)
Putting the value of a, c on the equation (1)
1 1 2
b 2 = (2 x − b )(2 y − b ) = 4 xy − 2by − 2 xb + b 2 or, by + xb = 2 xy or, + = (proved)
x y b
37. Let a and b two numbers . G be the geometric mean between a, b
a+q
two A.M p, q be inserted between a, b . ∴ G 2 = ab ----------- (1) p = or, a = 2 p − q
2
p+q
q= or, b = 2q − p
2
Putting the value of a, b on the equation (1) . G 2 = (2 p − q )(2q − p ) (proved)
a+b
38. Let a, b two numbers . By the question A = --------------- (1) ,
2
p2 q2
p 2 = aq or, a = , q 2 = pb or, b =
q b
p2 q2 p2 q2
Putting the value of a, b on the equation (1) 2 A = + or, + = 2 A (proved)
q p q p
39. By question t n2 = S n × 2d [ t n = nth term , S n = Sum of the n th term , a = first term ,
d = Common difference ]
2 n
or, {a + (n − 1)d } = {2a + (n − 1)d }× 2d
2
2
or, a + 2ad (n − 1) + (n − 1) d = 2and + n(n − 1)d 2
2

or, a 2 − 2ad + (n 2 − 2n + 1 − n 2 + n )d 2 = 0
2
or, a 2 − 2ad + d 2 = nd 2 or, (a − d ) = nd 2
a a
or, a − d = ± n d or,− 1 = ± n or, = 1 ± n
d d
∴ The ratio of the first term to the common difference is 1 ± n (proved)

9
40. Let three numbers are a − d , a, a + d .
The given condition a − d + a + a + d = 18 or, 3a = 18 or, a = 6
2
Again, (6 − d + 2 )(6 + d + 6 ) = (6 + 2 )
or, (8 − d )(12 + d ) = 8 2 or, 96 − 12d + 8d − d 2 = 64
or, − d 2 − 4d = −96 + 64
or, d 2 + 4d − 32 = 0 or, d 2 + 8d − 4d − 32 = 0
or, d (d + 8) − 4(d + 8) = 0 or, d = 4, d = −8
∴ Required numbers are 2,6,10 or, 14,6,−2 .
41. t 2 = ad [ a = first term , d = Common diff.] t8 = a + 7 d , t 32 = a + 31d
2
or, (a + 7 d ) = (a + d )(a + 31d ) [ By question] or, a 2 + 49d 2 + 14ad = a 2 + 31ad + ad + 31d 2
or, 18d 2 = 18ad or, 18d = 18a [ d ≠ 0 ] or, a = d
∴ The numbers are 2a,8a,32a ∴ Common ratio 4.
6 2
42. 666 ---------------- n times = [999 − − − − − − − n times ] = 10 n − 1
9 3
( )
8 n
Again 888 ---------------- n times = 10 − 1
9
( )
4
(
444 ---------------- 2n times = 10 2 n − 1
9
)
2
L.H.S, (666 − − − −n times ) + (888 − − − −n times )
2
2  8
( )
=  10 n − 1  + 10 n − 1 ( )
3  9
4 8 4
9
( 9
) ( 9
) [
= 10 2 n − 2.10 n + 1 + 10 n − 1 = 10 2 n − 2.10 n + 1 + 2.10 n − 2 ]
4
( )
= 10 2 n − 1 = 444 − − − − − 2n times (proved)
9
− 92 2
43. i) Common ratio ( r ) = =−
1 3
3
2 a 1 1
Q −1< − < 1 ∴ Sum = = 3 = .
3 (
1 − r 1 − − 23 5 )
0 ⋅ 81
ii) Common ratio ( r ) = = 0⋅9
0⋅9
a 0⋅9
Q − 1 < 0 ⋅ 9 < 1 ∴ Sum = = =9.
1− r 1− 0⋅9
3 3
iii) Common ratio ( r ) = 4 = > 1
1
2 2
Q r >1 ∴ Sum does not exist.
1 4
iv) Common ratio ( r ) = 12 = > 1
1
16 3
Q r >1 ∴ Sum does not exist.

10
44. Let, 1st term of the series be a and common ratio be r .
a
∴ Sum = = 3 (given)
1− r
or, a = 3(1 − r ) ………… (i)
8
Again, sum of 1st two terms =
3
8
or, a + ar =
3
8
or, a (1 + r ) =
3
8
or, 3(1 − r )(1 + r ) = (using (i))
3
8 1 1
or, 1 − r 2 = or, r 2 = or, r = ±
9 9 3
1  1 
Putting r = in (i), a = 31 −  = 2
3  3 
1  1
Putting r = − in (i), a = 31 +  = 4
3  3
∴ First term of the series is 2 or 4.
45. Let, first term = a and common ratio = r
t n = 3(t n +1 + t n + 2 + t n + 3 + − − − − − − − − −∞ ) ( t n = n th term)
(
or, ar n −1 = 3 ar n + ar n +1 + ar n + 2 + − − − − − − − − ∞ )
ar n
or, ar n −1 = 3 ⋅
1− r
or, 1 − r = 3r
1
or, r =
4
 1 4
Again, a + ar = 15 or, a1 +  = 15 or, a = 15 × = 12
 4 5
a 12 12 × 4
∴ Sum of the infinite series = = = = 16 .
1− r 1− 1 3
4

46. 0. 4 = 0 ⋅ 4444.....................................
= 0 ⋅ 4 + 0 ⋅ 04 + ⋅004 + ⋅0004 + ..................................... ∞
0⋅4 4
= =
1 9
1−
10
1
1 4 2 2
∴ (0 ⋅ 444 − − − − − − ) 2 =  = = 0 ⋅ 666 .................. . (Proved)
9 3
( ) ( )
47. L.H.S. = a(a + b ) + a 2 a 2 + b 2 + a 3 a 3 + b3 + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ upto ∞
= ( a 2 + a 4 + a 6 + ⋅ ⋅ ⋅ ⋅ upto infinite terms) + ( ab + a 2b 2 + a 3b3 + ⋅ ⋅ ⋅ ⋅ upto infinite terms)
a2 ab
= + (Q a < 1 and b < 1 ∴ a 2 < 1 and ab < 1 )
2
1 − ab
1− a
= R.H.S (Proved)

11
1
48. x = 1 + a + a 2 + ⋅ ⋅ ⋅ ⋅ ∞ = (Q − 1 < a < 1)
1− a
1 1
or, 1 − a = or, a = 1−
x x
1
Again, y = 1 + b + b 2 + ⋅ ⋅ ⋅ ⋅ ∞ = (Q − 1 < b < 1)
1− b
1 1
or, 1 − b = or, b = 1−
y y
L.H.S. = 1 + ab + a 2b 2 + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ∞
1
= (Q − 1 < a < 1 and − 1 < b < 1 ∴ − 1 < ab < 1 )
1 − ab
1 xy xy xy
= = = = = R.H.S. (Proved)
 1   1  xy − ( x − 1) ( y − 1) xy − xy + x + y − 1 x + y − 1
1 − 1 −  1 − 
 x  y
1 1 1 1
49. S1 = 1 + + + + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ upto infinite terms = =2
2 2 2 3 1
2 1−
2
2 2 2 2
S2 = 2 + + + + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ upto infinite terms = =3
3 32 33 1−
1
3
3 3 3 3
S3 = 3 + + + + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ upto infinite terms = =4
4 4 2 43 1−
1
4
n n n n
Sn = n + + + + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ upto infinite terms = = n +1
n + 1 (n + 1) 2 3 1
(n + 1) 1−
n +1
L.H.S. = S1 + S 2 + S3 + ⋅ ⋅ ⋅ ⋅ + S n = 2 + 3 + 4 + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ +(n + 1)
n n(n + 3)
= [2 + (n + 1)] = = R.H.S. (Proved)
2 2
50. Let, common ratio of the G.P. be r .
a a
∴S = or, r = 1 −
1− r S

∴ Sum of first n terms =


(
a 1− rn ) = [ a
]   a n 
1 − r n = S 1 − 1 −   (Proved)
1− r 1− r   S  

FUTURE GATE, C/23 School road, Sodepur 9830183298, 9062340430

12

You might also like